Humean laws for human agents - Hicks, Michael Townsen 1985-; Jaag, Siegfried; Loew, Christian (Oxford University Press, 2023)
"Humean Laws for Human Agents presents cutting-edge research by leading experts on the Humean account of laws, chance, possibility, and necessity. A central question in metaphysics and philosophy of science is: What are laws of nature? Humeans hold that laws are not sui generis metaphysical entities but merely particularly effective summaries of what actually happens. The most discussed recent work on Humeanism emphasizes the laws' usefulness for limited agents and uses pragmatic considerations to address fundamental and long-standing problems. The current volume develops and critically examines pragmatic Humean accounts, with innovative new work on the epistemology of laws and chance, the problem of induction, counterfactuals, special science laws, and a Humean account of essence. Taken together, the papers provide a roadmap for developing pragmatic Humeanism and connate views, setting the agenda for future research."--
Literaturangaben
Keywords: Hume, David -- 1711-1776; Naturgesetz; Hume, David / 1711-1776 / https://isni.org/isni/0000000121318235; Human beings / Philosophy; Physical laws / Philosophy; Metaphysics; Êtres humains / Philosophie; Lois physiques / Philosophie; Métaphysique; metaphysics; Hume, David / 1711-1776; Aufsatzsammlung